The effects of sclerotherapy with 5% trichloroacetic acid on the cyst diameter and ovarian tissue in the rat ovarian cyst model - Artas, Gokhan; Pala, Sehmus; Kuloglu, Tuncay; Atilgan, Remzi; Yavuzkir, Seyda; Akyol, Alparslan (Taylor & Francis Inc, 2018)
The aim of this study was to compare the effects of only aspiration with aspiration and 5% trichloroacetic acid (TCA) application on ovarian cyst size and ovarian reserve. The ovarian cysts of 14 rats that were divided into two groups randomly were investigated after total salpingectomy procedure. G1 was the group of saline application after cyst aspiration, while in G2, after aspiration 5% TCA at half amount of aspiration volume was injected into the cyst and re-aspirated after five minutes. The abdomens of the rats were closed and re-explored after 1month. The cyst diameters of the rats in each group were measured. Ovaries were removed for histopathological examination. There was no significant difference in cyst diameter in G1 before and after aspiration. In G2, there was a significant decrease in cyst size after TCA application. Ovarian follicle counts were not significantly different between the two groups. In conclusion, application of 5% TCA to the ovarian cysts for five minutes significantly reduces the cyst size.Impact StatementWhat is already known on this subject: Minimally invasive therapies come into prominence to avoid surgical complications and diminished fertility in the treatment of ovarian cysts. USG-guided aspiration and sclerosis has been reported as cost-efficient and effective treatment methods for localised benign cysts in other organs such as the thyroid, parathyroid, liver, kidney and spleen. It has been shown that sclerotherapy applied to infertile women with ovarian cysts reduces pelvic pain without affecting the number of follicles, term pregnancy and abortion rates, extracted oocytes, embryo quality or hormonal levels when compared to non-ovarian cystic infertile women. TCA is a chemical agent that is topically applied, not systemically absorptive, which causes denaturation of proteins and structural cell death, resulting in coagulation necrosis after chemical cauterisation. For this reason, we used 5% TCA to treat simple ovarian cysts on a rat model.What the results of this study add: In this experimental study, we showed that the application of 5% TCA into the cyst for five minutes - then aspirated - significantly reduced the size of the ovarian cysts. Five percent TCA application did not affect the ovarian reserve.What the implications are of these findings for clinical practice and/or further research: Our study is original because of the fact that to the best of our knowledge, this is the first study about the use of 5% TCA in treatment of ovarian cysts in the literature.
Keywords: Ovarian cyst model; trichloroacetic acid; ovarian reserve; rat